2015
DOI: 10.1002/ejhf.229
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intravenous ferric carboxymaltose on renal function: an analysis of theFAIR‐HFstudy

Abstract: AimsAnaemia and iron deficiency are constituents of the cardio-renal syndrome in chronic heart failure (CHF). We investigated the effects of i.v. iron in iron-deficient CHF patients on renal function, and the efficacy and safety of this therapy in patients with renal dysfunction.Methods and resultsThe FAIR-HF trial randomized 459 CHF patients with iron deficiency (ferritin <100 µg/L, or between 100 and 299 µg/L if transferrin saturation was <20%): 304 to i.v. ferric carboxymaltose (FCM) and 155 to placebo, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 56 publications
1
56
0
10
Order By: Relevance
“…Administration of iron to iron-deficient cardiorenal syndrome patients has recently been shown to improve their renal function. 28 Comparison of oral versus intravenous iron administration across the spectrum of CKD aetiologies currently favours the intravenous route in terms of iron repletion efficacy and reduction in reliance on ESAs, with a good reported safety profile. 29,30 Clinical guidelines suggest haemoglobin levels should not be maintained above 11.5 g/dL by ESA therapy, and that selection of the route of iron administration should be based on severity of the anaemia and iron deficiency, prior response or intolerance to treatments, availability of venous access, cost implications and current ESA use.…”
mentioning
confidence: 99%
“…Administration of iron to iron-deficient cardiorenal syndrome patients has recently been shown to improve their renal function. 28 Comparison of oral versus intravenous iron administration across the spectrum of CKD aetiologies currently favours the intravenous route in terms of iron repletion efficacy and reduction in reliance on ESAs, with a good reported safety profile. 29,30 Clinical guidelines suggest haemoglobin levels should not be maintained above 11.5 g/dL by ESA therapy, and that selection of the route of iron administration should be based on severity of the anaemia and iron deficiency, prior response or intolerance to treatments, availability of venous access, cost implications and current ESA use.…”
mentioning
confidence: 99%
“…Twenty-four weeks from commencing treatment with iron or placebo, the symptoms, functional capacity and quality of life were significantly better among patients receiving iron repletion than in the placebo-treated patients; rates of adverse events did not differ between the groups. The effects of iron supplementation were observed regardless of the presence of anemia, and iron treatment was associated with a modest but significant improvement in renal function (difference in estimated glomerular filtration rate 2.98 ml/ min/1.73 m 2 at week 24) [33] . The Ferric Carboxymaltose Evaluation on Performance in Patients with Iron Deficiency in Combination with Chronic Heart Failure (CONFIRM-HF) trial is another recently published RCT that examined the effects of iron treatment for approximately 1 year in 304 ambulatory symptomatic heart failure patients who had nearly identical iron profiles as those of the subjects in the FAIR-HF trial [34] .…”
Section: Iron and Cardiovascular Riskmentioning
confidence: 97%
“…33 A later analysis of these same patients showed that renal function was enhanced with iron as well. 34 Despite these persuasive findings, routine screening for iron deficiency did not become a standard practice in most HF programs. Accordingly, the Ferric Carboxymaltose Evaluation on Performance in Patients With Iron Deficiency in Combination With Chronic Heart Failure (CONFIRM-HF) trial was undertaken to address the sustainability of iron's beneficial effects.…”
Section: Iron Therapymentioning
confidence: 99%